2017
DOI: 10.1002/2016jc012629
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐optical anomalies in the world's oceans: An investigation on the diffuse attenuation coefficients for downward irradiance derived from Biogeochemical Argo float measurements

Abstract: Identification of oceanic regions characterized by particular optical properties is extremely important for ocean color applications. The departure from globally established bio‐optical models (i.e., anomaly) introduces uncertainties in the retrieval of biogeochemical quantities from satellite observations. Thanks to an array of 105 Biogeochemical Argo floats acquiring almost daily downward irradiance measurements at selected wavelengths in the UV and blue region of the spectrum, we reexamined the natural vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 104 publications
4
68
0
3
Order By: Relevance
“…For specific examples based on same PROVOR CTS4 profiling floats included in this study, the reader is referred to the works by Dall'Olmo and Mork (2014) and for estimation and analysis of particulate organic carbon concentrations and fluxes; Lacour et al (2017), Mignot et al (2017), and Stanev et al (2017) for observing the impact of physical drivers on biology; and Organelli et al (2017) and Barbieux et al (2017b) for analysis of the variability in diffuse attenuation coefficients for downward irradiance and particulate optical backscattering-to-chlorophyll ratios across different oceanic areas, respectively. It is worth noting that the latter two studies have been pursued by exclusively exploiting BOPAD-surf and BOPAD-prof.…”
Section: Conclusion and Recommendations For Usementioning
confidence: 99%
See 1 more Smart Citation
“…For specific examples based on same PROVOR CTS4 profiling floats included in this study, the reader is referred to the works by Dall'Olmo and Mork (2014) and for estimation and analysis of particulate organic carbon concentrations and fluxes; Lacour et al (2017), Mignot et al (2017), and Stanev et al (2017) for observing the impact of physical drivers on biology; and Organelli et al (2017) and Barbieux et al (2017b) for analysis of the variability in diffuse attenuation coefficients for downward irradiance and particulate optical backscattering-to-chlorophyll ratios across different oceanic areas, respectively. It is worth noting that the latter two studies have been pursued by exclusively exploiting BOPAD-surf and BOPAD-prof.…”
Section: Conclusion and Recommendations For Usementioning
confidence: 99%
“…In addition, the array provided measurements of the underwater light field (i.e., irradiance) and of the inherent optical properties (i.e., particulate optical beam attenuation and backscattering coefficients) of the oceans. All these measurements, and derived quantities, are useful for both biogeochemical and bio-optical studies, to address the variability in biological processes (e.g., phytoplankton phenology and primary production; Lacour et al, 2015) and linkages with physical drivers (Boss et al, 2008;Boss and Behrenfeld, 2010;Lacour et al, 2017;Mignot et al, 2017;Stanev et al, 2017), to estimate particulate organic carbon concentrations and export (e.g., Bishop et al, 2002;Dall'Olmo and Mork, 2014;, and to support satellite missions through validation of bio-optical products retrieved from ocean color remote sensing (e.g., chlorophyll concentration; Claustre et al, 2010b;IOCCG, 2011IOCCG, , 2015Gerbi et al, 2016;Haëntjens et al, 2017) or by identification of those regions with bio-optical behaviors departing from mean-statistical trends (i.e., bio-optical anomalies; Organelli et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Supporting Information: Supporting Information S1 Supporting Information S2 Supporting Information S3 Table S1 Table S2 Table S3 The recently launched network of BGC-Argo profiling floats is progressively transforming our capability to observe optical properties and biogeochemical processes in the oceans (Biogeochemical-Argo Planning Group, 2016; Claustre et al, 2010;IOCCG, 2011;Johnson & Claustre, 2016). The current BGC-Argo bio-optical database has drastically increased over recent years and now encompasses observations collected in a broad range of hydrological, trophic, and bio-optical conditions encountered in the world's open oceans (Organelli et al, 2017a(Organelli et al, , 2017b. Based on homogeneous measurements and processing methodologies, this database offers a unique opportunity to comprehensively reassess bio-optical relationships.…”
Section: Introductionmentioning
confidence: 99%
“…While the variations in a ph (λ) and a nap (λ) have been extensively studied in various area of the global ocean (Bricaud et al, ; Boss et al, ; Devred et al, ; Lutz et al, ; Suzuki et al, ), few studies have been performed in the Red Sea (Brewin et al, , Organelli et al, ) during the last three decades. Recently, Brewin et al () suggested that the Red Sea waters and their optical characteristics can be affected by its different hydrological, biological and environmental conditions (low precipitation, little riverine input, and desert dust events), giving rise to distinct bio‐optical relationships in some subareas of this sea.…”
Section: Introductionmentioning
confidence: 99%